Estudio de factibilidad para la creación de una empresa comercializadora de artesanías a base de fique en la ciudad de Santiago de Cali (2015)
The feasibility study for the creation of the Global crafts del Cauca fique based, is a company dedicated to the marketing of handicrafts produced in the plant called sisal; consumption trend is based on sisal growing and sustained demand for products produced with cleaner production methods, resulting in a lower environmental impact, as well as specific demands for organic products, certification attesting to the non-use of chemicals in cultivation. Market research supports the conclusion that high degree of acceptance of marketing there, also enables the analysis of demand and supply, developing business strategies by determining the viability of the project. It is on this basis continues as technical studies in which the location is determined, size, capacity and project engineering, organizational and legal aspects study determines the administrative structure and legal requirements necessary to implement the company. Finally in the financial study, total investment costs, product pricing, as well as the profitability and feasibility, based on the decision criteria is considered. We conclude that analyzing each of the studies can affirm the feasibility of the creation of the company.